Identification of a cytotoxic molecule in heat-modified citrus pectin. (10th February 2016) - Leclere, Lionel; Fransolet, Maude; Cambier, Pierre; El Bkassiny, Sandy; Tikad, Abdellatif; Dieu, Marc; Vincent, Stéphane P.; Van Cutsem, Pierre; Michiels, Carine
Highlights: Heat-fragmented pectin contains 4, 5-dihydroxy-2-cyclopenten-1-one. 4, 5-Dihydroxy-2-cyclopenten-1-one is cytotoxic for cancer cells. This molecule induces similar features of apoptosis as heat-treated pectin does. Abstract: Modified forms of citrus pectin possess anticancer properties. However, their mechanism of action and the structural features involved remain unclear. Here, we showed that citrus pectin modified by heat treatment displayed cytotoxic effects in cancer cells. A fractionation approach was used aiming to identify active molecules. Dialysis and ethanol precipitation followed by HPLC analysis evidenced that most of the activity was related to molecules with molecular weight corresponding to low degree of polymerization oligogalacturonic acid. Heat-treatment of galacturonic acid also generated cytotoxic molecules. Furthermore, heat-modified galacturonic acid and heat-fragmented pectin contained the same molecule that induced cell death when isolated by HPLC separation. Mass spectrometry analyses revealed that 4, 5-dihydroxy-2-cyclopenten-1-one was one cytotoxic molecule present in heat-treated pectin. Finally, we synthesized the enantiopure ( 4R, 5R )-4, 5-dihydroxy-2-cyclopenten-1-one and demonstrated that this molecule was cytotoxic and induced a similar pattern of apoptotic-like features than heat-modified pectin.